Drug Delivery: Thiolation and Cell‐Penetrating Peptide Surface Functionalization of Porous Silicon Nanoparticles for Oral Delivery of Insulin (Adv. Funct. Mater. 20/2016). (May 2016) - Shrestha, Neha; Araújo, Francisca; Shahbazi, Mohammad‐Ali; Mäkilä, Ermei; Gomes, Maria João; Herranz‐Blanco, Bárbara; Lindgren, Rici; Granroth, Sari; Kukk, Edwin; Salonen, Jarno; Hirvonen, Jouni; Sarmento, Bruno; et al.
Abstract : Mucoadhesive and cell‐associating porous silicon‐based nanoparticles for oral delivery of insulin are described by N. Shrestha, H. A. Santos, and co‐workers on page 3405. Using a highly efficient top‐down approach and simple crosslinking chemistry, porous silicon nanoparticles (NPs) are modified withl ‐cysteine‐ and cell‐penetrating‐peptides to enhance permeation of insulin across the intestine wall, through the close proximity to the intestinal epithelia.